2004
DOI: 10.1007/s00428-004-1129-7
|View full text |Cite
|
Sign up to set email alerts
|

CD10 expression in diffuse large B-cell lymphomas does not influence survival

Abstract: CD10 expression is considered as a marker of centrofollicular-derived diffuse large B-cell lymphomas (DLBCL). The aim of our study was to determine retrospectively among 98 patients with DLBCL, enrolled in the LNH93 trial of the Groupe d'Etude des Lymphomes de l'Adulte (GELA) and homogeneously treated with high-dose cyclophosphamide, doxorubicin, vincristine and prednisone (CHOP)-like regimen [doxorubicin, cyclophosphamide, vindesine, bleomycin and prednisone (ACVBP)], the expression of CD10 using immunohistoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 28 publications
0
22
0
3
Order By: Relevance
“…Previous studies that applied the same cutoff value of 10% reported a lower frequency of positive expression of CD10 [19% (Braaten et al, 2003), 34% (Fabiani et al, 2004), 43% (Xu et al, 2001), and 51% (Linderoth et al, 2003)] Other studies, using the 20%, 25%, 30% and 50% cutoff values reported a wide range of CD10 expression in DLBCL tumors (2 to 92%) (e.g. Harada et al, 1999;Ohshima et al, 2001;Pileri et al, 2003;Camilleri-Broet et al, 2006).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Previous studies that applied the same cutoff value of 10% reported a lower frequency of positive expression of CD10 [19% (Braaten et al, 2003), 34% (Fabiani et al, 2004), 43% (Xu et al, 2001), and 51% (Linderoth et al, 2003)] Other studies, using the 20%, 25%, 30% and 50% cutoff values reported a wide range of CD10 expression in DLBCL tumors (2 to 92%) (e.g. Harada et al, 1999;Ohshima et al, 2001;Pileri et al, 2003;Camilleri-Broet et al, 2006).…”
Section: Discussionmentioning
confidence: 96%
“…However, other studies boasted respectable sample sizes of CD10 positive patients (ranging from 27 to 63) (Colomo et al, 2003;Linderoth et al, 2003;Fabiani et al, 2004;Liu et al, 2008) and still did not find a significant association between CD10 expression and DLBCL survival.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Thirty-three percent positivity of CD10 was similar to previous reports. 11,12,14,24,29,30 The misclassification rate for the modified classification was 14% in relation to the Hans algorithm and 16% in relation to the Muris algorithm. According to Kappa statistics, the mea- …”
Section: Patient Characteristicsmentioning
confidence: 93%